Coastal tourism as an alternative solution to poverty alleviation in remote village communities in soto'ó village, south nias - Tafonao, Aluiwaauri; Duha, Timotius (Institute of Computer Science (IOCS), 2025)
Soto'o Village has great potential to be developed as a leading coastal tourism destination in South Nias. However, its management remains very limited and seems to be stagnant. As a result, Soto'o Village is less well-known as a tourist destination. This study aims to: (1) describe the importance of coastal tourism as a strategy to improve the local economy through a community-based and sustainable approach. (2) analyze the coastal tourism potential in Soto'o Village, including aspects of natural beauty, culture, and local wisdom; identify supporting and inhibiting factors for coastal tourism development in the village; and formulate a strategy for developing sustainable community-based coastal tourism, taking into account social, economic, and environmental aspects. This study used a qualitative approach with direct observation of tourism potential and existing infrastructure conditions. This was achieved through interviews and focus group discussions (FGDs). The results indicate that Soto'o Beach is worthy of being developed as a new coastal tourism destination in South Nias due to its natural and marine beauty. Village residents strongly support their village as a new tourist destination. The Soto'o village government, the Maniamolo sub-district head and his staff, academics, students, and community leaders agreed to encourage the South Nias Regency Government to support this initiative through sustainable infrastructure development in Soto'o village. It is hoped that coastal tourism activities will provide the potential to increase the income of Soto'o villagers